Cultural aspects in the lexicographical discourse of the early twentieth century: The national linguistic identity in the Nuevos Chileanismos dictionary (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
This work offers an analysis of the New Chileanisms dictionary with the objective of identifying the main cultural aspects present in this Chilean work of the beginning of the XXth century. Thanks to a methodological approach based on grounded theory, it is possible to establish that within the cultural aspects with greater presence highlights the conformation of Chilean linguistic identity, which is evidenced through the social assessment offered by the author of the national standard and, in addition, the opposition established between it and the peninsular norm.
Keywords: Lexicography; New chilenisms dictionary; chilean linguistic identity